2016
DOI: 10.1007/s00259-015-3286-0
|View full text |Cite
|
Sign up to set email alerts
|

Excretion of radionuclides in human breast milk after nuclear medicine examinations. Biokinetic and dosimetric data and recommendations on breastfeeding interruption

Abstract: Based on an effective dose limit of 1 mSv to the infant and a typical administered activity, we recommend cessation of breastfeeding for (131)I-NaI and interruption of feeding for 12 h for (125)I-iodohippurate, (131)I-iodohippurate, (99m)Tc-pertechnetate and (99m)Tc-MAA. During this 12-h period all breast milk should be expressed at least three times and discarded. For the other radiopharmaceuticals included in this study, no interruption of breastfeeding is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
28
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 37 publications
0
28
0
6
Order By: Relevance
“…A 12-hour interruption has also been recommended for I-iodo-hippurate [3]. The %ID in breast milk is higher for Tc-labelled compounds (<0.1 %).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…A 12-hour interruption has also been recommended for I-iodo-hippurate [3]. The %ID in breast milk is higher for Tc-labelled compounds (<0.1 %).…”
mentioning
confidence: 99%
“…Unfortunately, the study by Leide-Svegborn et al [3] Tc-pertechnetate in breast milk is the presence of a sodium iodide symporter in mammary gland cells [7], which leads to a significantly higher radioactivity concentration in breast milk than in maternal plasma. The study by Leide-Svegborn et al [3] showed a lower excretion of radioactivity in breast milk after pretreatment with the thyroid blocking agent perchlorate: after 99m Tc-pertechnetate administration without blocking a 10 %ID in breast milk was found compared with a significantly lower 0.82 %ID with blocking. These data are supported by animal data from mouse mammary gland cells which also show blocking of the sodium iodide symporter by perchlorate [7].…”
mentioning
confidence: 99%
See 3 more Smart Citations